2019
DOI: 10.1167/iovs.18-26325
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses of the Anterior Ventral Occipitotemporal Cortex in Developmental Dyslexia: Beyond the Visual Word Form Area

Abstract: PURPOSE. For the past 2 decades, neuroimaging studies in dyslexia have pointed toward a hypoactivation of the ventral occipitotemporal cortex (VOTC), a region that has been closely associated to reading through the extraction of a representation of words which is invariant to position, size, font or case. However, most of the studies are confined to the visual word form area (VWFA), while recent studies have demonstrated a posterior-to-anterior gradient of print specificity along the VOTC. In our study, the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…The question of whether the VWFA plays a role in DD has been addressed by some investigators by examining the excitability of the VWFA using mainly fMRI. In several fMRI studies, subjects with dyslexia showed reduced activation in the classic VWFA [233][234][235], and the adjacent anterior regions of the left fusiform gyrus compared to normal readers [236][237][238][239][240][241][242][243][244]. Reduced activation of the word form area that is part of the left ventral occipital cortex is a common finding in subjects with dyslexia [179,180,188,193,194,222,229,232,[245][246][247][248][249][250].…”
Section: A Hierarchy Of Visual Processingmentioning
confidence: 99%
“…The question of whether the VWFA plays a role in DD has been addressed by some investigators by examining the excitability of the VWFA using mainly fMRI. In several fMRI studies, subjects with dyslexia showed reduced activation in the classic VWFA [233][234][235], and the adjacent anterior regions of the left fusiform gyrus compared to normal readers [236][237][238][239][240][241][242][243][244]. Reduced activation of the word form area that is part of the left ventral occipital cortex is a common finding in subjects with dyslexia [179,180,188,193,194,222,229,232,[245][246][247][248][249][250].…”
Section: A Hierarchy Of Visual Processingmentioning
confidence: 99%
“…There is much evidence to suggest that injury to the left occipitotemporal area can lead to impaired reading ability, including pure alexia 87 , 88 or transient alexia 89 . Consistently, developmental dyslexia (in the absence of brain damage) is instead associated with insufficient or atypical activation of the left occipito-temporal ventral cortex activation for words 88 , 90 96 . This atypical or insufficient activity would result in smaller amplitudes of the left occipital/temporal N170 in response to words that symbols 91 , 97 , as compared to controls.…”
Section: Discussionmentioning
confidence: 82%
“…However, phase-shuffled words were employed as an alternative comparison for exploratory analyses, with equal spatial-frequency amplitude and permuted spatial-frequency phase. Similar phase-shuffled word stimuli have shown robust differences to word forms in fMRI investigations of vOT activity (Rauschecker et al, 2012; Rodrigues et al, 2019; White et al, 2019; Yeatman et al, 2013).…”
Section: Methodsmentioning
confidence: 99%